THE LANGUAGE CONSTRUCTION OF CHILDREN PUBLIC SERVICE ADVERTISEMENT ANIMATED VERSION WASPADA CORONA IN ONLINE MEDIA AND THE CONSTRUCTION OF THE SOCIETY IN SEMARANG CITY - Dian Marhaeni Kurdaningsih; Genta Maghvira (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
This research is motivated by the presence of advertisements in online media dealing with the worldwide Covid-19 pandemic. Advertisement with children as the endorser to convey the message on Waspada Corona aired in animated version of public service advertisement. this advertisement is very intriguing seen from the emerge of children in educating the public dealing with the enormity and serious impact of the epidemic. How online media construct the children animated advertising language on waspada Corona and how the Semarang society reconstruct language message in the media. This research purposive media text selection as the data collecting method and media text analysis in its analyzing technique as analyzing advertisement method. While the construction of the society, the data were analyzed by mans of Miles and Huberman’s interactive and constructivist qualitative analysis. The paradigm used is constructivism and is completed with Peter L berger’s social construction theory. The result of this research are expecyed to show the full form of construction of children advertisement in online media and the construction of the society in responding the online media advertising messages. Keywords : Animation, Children advertisement, Construction, Online Media, Public Service Advertisement.